A formação continuada de professores/as sobre gênero e sexualidade: contribuições para uma nova prática pedagógica - Martins, Aline Madalena (2019)
The present research refers to the experience of continuing education of teachers of the public network in the theme gender and sexuality and their contributions to a new teaching practice aiming at a quality education. The research is part of the set of scientific productions that seek to know how the schools and the subjects that integrate it deal with these issues and highlights the importance of continuing education for teachers, in the perspective of opportunizing, during their career, the improvement and the acquisition of new knowledge. It is based on the understanding that continuing education in gender and sexuality can, through experience and reflection on the conceptions presented, generate new pedagogical practices articulated in the history of the struggle of feminist and lesbian, gay, bisexual and transgender social movements (LGBT), to end gender inequality and gender discrimination. The general objective is to analyze the processes of change between teachers involved in Continuing Education on Gender and Sexuality and the repercussions on teaching practices. In order to serve it, it was identified as specific objectives: to identify if there were changes in relation to the conceptions of gender among teachers; investigate teachers' practices after participating in continuing education; and, finally, to analyze to what extent the changes of conception allowed new pedagogical practices. The research is based on the historical and dialectical materialist approach to which the human being is historical and social, determined by the economic, political and cultural contexts, but capable of transforming social reality. Education, also determined in these contexts, is a space for action by individuals capable of promoting transformations or maintaining existing contradictions if it reinforces class, sexist and racist hegemony. In order to understand the experiences and practices of the teachers, nine professionals were interviewed who had the opportunity to participate in an ongoing training on gender and sexuality offered in partnership with PPGE-Unisul in a full-time Municipality of Tubarão in the year 2014. The interviews were carried out from a semi-structured and individual itinerary. As a theoretical reference, Marxist references from E.P. Thompson (1981; 1987) and concepts such as experience, culture and social conscience were adopted; the studies on gender of Carvalho (2011), Connell (1990; 2013), Louro (2001) and Vianna (2012; 2015); on education and continuing education, Fossatti (2013), Giroux (1995), Nóvoa (2013), Pimenta (1995, 1996), Tardif (2012) and other works found in the production survey on the subject were used. point to the incorporation of critical pedagogical practices in relation to gender binaries in teachers who continue to work in the school unit, but without repercussion in activities related to sexuality. In addition, the school manager was seen by the interviewees as a point of reference for work focused on gender issues in school. Already for the teachers to other school units, despite the questioning of sexism in education, there was no incorporation of new teaching practices.